NURSING CARE FOR SENSORY PERCEPTION DISTURBANCE: VISUAL HALLUCINATIONS IN MR. S WITH A FOCUS ON DHIKR INTERVENTION AT DR. RM SOEDJARWADI REGIONAL MENTAL HOSPITAL, KLATEN - Asiah, Yayuk Nur; Fida dyah Puspasari; Sudiarto (PT. Jurnal Center Indonesia Publisher, 2025)
Background: Visual hallucinations are sensory perception disturbances in which individuals perceive objects or shadows that do not actually exist, even though they appear vivid and real. Therefore, nursing interventions are needed to reduce the occurrence of visual hallucinations in patients, one of which is through dzikir (remembrance of Allah). Linguistically, dzikir comes from the word dzakar, which means remembering. Remembering Allah implies maintaining one’s consciousness toward Him by following specific etiquettes prescribed in the Qur’an and Hadith. The purpose of dzikir is to purify the heart and glorify Allah SWT. Purpose: To determine the implementation of nursing care for patients with sensory perception disturbances: visual hallucinations, with a focus on dzikir practice. Method: This study used a descriptive method in the form of a case study. Results: The case study showed that the patient was able to carry out SP 1–3 with a focus on dzikir practice, as indicated by behavioral changes such as feeling calmer, being able to recite dzikir independently, and experiencing reduced hallucinations. This suggests that dzikir is quite effective. Conclusion: Nursing care for patients with sensory perception disturbances, specifically visual hallucinations, with a focus on dzikir intervention over three days, can help control hallucinations